Synthesis, Structure, DNA Interaction, and SOD Activity of Three Nickel(II) Complexes Containing L-Phenylalanine Schiff Base and 1,10-Phenanthroline - Peiran Zhao; Shanshan Zhai; Jianfang Dong; Lei Gao; Xinru Liu; Lei Wang; Jinming Kong; Lianzhi Li (Bioinorganic Chemistry and Applications)
Three hexacoordinated octahedral nickel(II) complexes, [Ni(sal-L-phe)(phen)(CH3OH)]⋅CH3OH (1), [Ni(naph-L-phe)(phen)(CH3OH)] (2), and [Ni(o-van-L-phe)(phen)(CH3OH)]⋅5CH3OH (3) (sal-L-phe = a Schiff base derived from salicylaldehyde and L-phenylalanine, naph-L-phe = a Schiff base derived from 2-hydroxy-1-naphthaldehyde and L-phenylalanine, o-van-L-phe = a Schiff base derived from o-vanillin and L-phenylalanine, and phen = 1,10-phenanthroline), have been synthesized and characterized by elemental analysis, IR spectra, and single-crystal X-ray diffraction. The interactions of these complexes with CT-DNA were studied by UV-Vis absorption spectroscopy, fluorescence spectroscopy, circular dichroism spectroscopy, and viscosity measurements. The binding constant (Kb) values of 1.82 × 104 M−1 for 1, 1.96 × 104 M−1 for 2, and 2.02 × 104 M−1 for 3 suggest that each of these complexes could bind with DNA in a moderate intercalative mode. Complex 3 exhibited a stronger interaction with CT-DNA than complexes 1 and 2. In addition, the superoxide scavenging activity of these complexes was investigated by the nitrotetrazolium blue chloride (NBT) light reduction method, and the results showed that they exhibited a significant superoxide scavenging activity with the IC50 values of 4.4 × 10−5 M for complex 1, 5.6 × 10−5 M for complex 2, and 3.1 × 10−5 M for complex 3, respectively.